Line Source Scattering by Dielectric Objects inside a Circular Cylinder with Resistive Boundary - Part 2: Inverse Scattering - (:unkn) unknown (IEEE, 2019)
In the second part of the two-part paper, the inverse problem considered is to recover the shape, the physical properties and the location of cylindrical objects embedded in a circular cylinder having resistive boundary. The cylindrical structure is excited by a monochromatic line source. The approach for the inverse problem is exactly the same as given in Yelkenci [1]. The solution is achieved by the Born approximation of the related integral equation. In the companion Paper-1, the scattered field was discussed. Part-2 reveals the reconstruction procedure.